2014
DOI: 10.1007/s10096-014-2224-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk of intrauterine growth restriction among HIV-infected pregnant women: a cohort study

Abstract: The purpose of this investigation was to study the risk of intrauterine growth restriction in human immunodeficiency virus (HIV)-infected women and to describe the associated risk factors. A cohort study was performed among HIV-infected women who delivered in a single tertiary centre in Barcelona, Spain, from January 2006 to December 2011. Consecutive singleton pregnancies delivered beyond 22 weeks of pregnancy were included. Intrauterine growth restriction (IUGR) was defined as a birth weight below the 10th c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 46 publications
0
19
0
1
Order By: Relevance
“…For example, individuals infected with influenza produce a lower proportion of preterm births (8.0%) and low birth weight newborns (4.7%) (Acs, Banhidy, Puho, & Czeizel, 2006;Doyle, Goodin, & Hamilton, 2013;S. S. Lee & Wong, 2012); women with circulating hepatitis B virus (HBV) DNA show a higher proportion of spontaneous preterm births (7.3%) than women without HBV infection (1.6%) (Elefsiniotis, et al, 2010;Mouloudi, et al, 2012;Sirilert, Traisrisilp, Sirivatanapa, & Tongsong, 2014); the incidence of preterm delivery is 19.7% in human immunodeficiency virus (HIV)-infected women and 8.5% in healthy women (López, et al, 2016;Lopez, et al, 2012;Lopez, et al, 2015;Rollins, et al, 2007;Uneke, Duhlinska, & Ujam, 2009); prematurity is 77% higher in infants of mothers with malaria caused by Plasmodium falciparum than in infants of mothers with malaria by caused by Plasmodium vivax (Botto-Menezes, et al, 2015;Nair & Nair, 1993;Tobon-Castano, Solano, Sanchez, & Trujillo, 2011). In addition, urogenital infections during pregnancy, such as bacterial vaginosis (Klebanoff, et al, 2005), placental malaria infection (Menendez, et al, 2000;Oraneli, Okeke, & Ubachukwu, 2013), Chlamydia trachomatis infection (Baud, et al, 2015;Rours, et al, 2011), schistosomiasis (Mombo-Ngoma, et al, 2017),…”
Section: Maternal Hot and Cold Inflammation-induced Preterm Birth Andmentioning
confidence: 99%
“…For example, individuals infected with influenza produce a lower proportion of preterm births (8.0%) and low birth weight newborns (4.7%) (Acs, Banhidy, Puho, & Czeizel, 2006;Doyle, Goodin, & Hamilton, 2013;S. S. Lee & Wong, 2012); women with circulating hepatitis B virus (HBV) DNA show a higher proportion of spontaneous preterm births (7.3%) than women without HBV infection (1.6%) (Elefsiniotis, et al, 2010;Mouloudi, et al, 2012;Sirilert, Traisrisilp, Sirivatanapa, & Tongsong, 2014); the incidence of preterm delivery is 19.7% in human immunodeficiency virus (HIV)-infected women and 8.5% in healthy women (López, et al, 2016;Lopez, et al, 2012;Lopez, et al, 2015;Rollins, et al, 2007;Uneke, Duhlinska, & Ujam, 2009); prematurity is 77% higher in infants of mothers with malaria caused by Plasmodium falciparum than in infants of mothers with malaria by caused by Plasmodium vivax (Botto-Menezes, et al, 2015;Nair & Nair, 1993;Tobon-Castano, Solano, Sanchez, & Trujillo, 2011). In addition, urogenital infections during pregnancy, such as bacterial vaginosis (Klebanoff, et al, 2005), placental malaria infection (Menendez, et al, 2000;Oraneli, Okeke, & Ubachukwu, 2013), Chlamydia trachomatis infection (Baud, et al, 2015;Rours, et al, 2011), schistosomiasis (Mombo-Ngoma, et al, 2017),…”
Section: Maternal Hot and Cold Inflammation-induced Preterm Birth Andmentioning
confidence: 99%
“…A high rate of IUGR has been observed among HIV pregnancies, probably due to placental insufficiency. 12 HIV infection in mother itself can cause IUGR. 13 SGA babies are at a higher risk for peripartum HIV transmission but in our study all four babies who found HIV positive, had birth weight ≥2.5kg, hence further research is needed to study the mechanism of transmission in relation to birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…Lopez et al reported 23.4% for cases of IUGR diagnosed antenatally. Two thirds of those cases were associated with abnormal umbilical artery Doppler study, which indicates placental insufficiency [3]. The Women and Infants Transmission Study (WITS) reported 21% for cases of preterm births and 19% for cases of low birth weight, while Lambert et al reported 17% and 13% for cases of low birth weight and IUGR in HIV-positive women respectively.…”
Section: Review Of Apoptosismentioning
confidence: 99%
“…The Women and Infants Transmission Study (WITS) reported 21% for cases of preterm births and 19% for cases of low birth weight, while Lambert et al reported 17% and 13% for cases of low birth weight and IUGR in HIV-positive women respectively. Neonates with IUGR were associated with iatrogenic preterm birth and needed a longer NICU stay [3][4][5]. Mittal et al reported that in a group of patients who received longer cART, the incidence of IUGR was 27%, which was associated with apoptosis-related placental insufficiency [6].…”
Section: Review Of Apoptosismentioning
confidence: 99%